Effect of E-Service Quality and E-Trust on E-Loyalty of E-Payment Through E-Satisfaction of Shopee pay Users - Ajeng Atha Ardelia Cahyanti; Sudarmiatin; Titis Shinta Dhewi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The industrial world has begun to enter the 5.0 era which marked by increasingly advanced technological developments. One of the them is the development of digital wallets that make people to pay online or offline easier. People do not need to carry cash, they can buy whatever they want only through online applications, one of which is ShopeePay. This research is a type of quantitative research with a descriptive research design using SPSS 25 and path analysis techniques. ShopeePay users who use more than three times of use amounted to 200 respondents by using the Lemeshow formula aid. The results of this study indicate that (1) e-service quality have a positive and significant direct effect on e-loyalty, (2) e-trust have a positive and significant direct effect on e-loyalty, (3) e-satisfaction has a positive and significant direct effect on e-loyalty, (4) e-service quality has a positive and significant direct effect on e-satisfaction, (5) e-Trust has a positive and significant direct effect on e-satisfaction, (6) e-service quality have a positive and significant indirect effect on e-loyalty through e-satisfaction, dan. (7) e-trust have a positive and significant indirect effect on e-loyalty through e-satisfaction In the results of this study, researchers have suggestions for ShopeePay companies to continue to innovate, develop, and maintain as well as to improve quality to the trust of customers.